2011
DOI: 10.1016/j.jcmg.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Improves Angina in Women With Evidence of Myocardial Ischemia But No Obstructive Coronary Artery Disease

Abstract: In women with angina, evidence of ischemia, and no obstructive CAD, this pilot randomized, controlled trial revealed that ranolazine improves angina. Myocardial ischemia may also improve, particularly among women with low CFR. These data document approach feasibility and provide outcome variability estimates for planning a definitive large clinical trial to evaluate the role of ranolazine in women with microvascular coronary dysfunction. (Microvascular Coronary Disease In Women: Impact Of Ranolazine; NCT005700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 34 publications
3
100
2
3
Order By: Relevance
“…One pilot study showed improved symptoms in women with angina, evidence of ischemia but no obstructive CAD, and patients with low CFR demonstrated improved CFR with treatment. 106 A similar-sized study showed some improvement in symptoms but no effect on coronary microvascular function. 107 A recent large randomized trial of a 2-week course of ranolazine vs. placebo found no difference in symptoms or myocardial perfusion reserve.…”
Section: Invasive Testingmentioning
confidence: 92%
“…One pilot study showed improved symptoms in women with angina, evidence of ischemia but no obstructive CAD, and patients with low CFR demonstrated improved CFR with treatment. 106 A similar-sized study showed some improvement in symptoms but no effect on coronary microvascular function. 107 A recent large randomized trial of a 2-week course of ranolazine vs. placebo found no difference in symptoms or myocardial perfusion reserve.…”
Section: Invasive Testingmentioning
confidence: 92%
“…In addition, ranolazine might also improve coronary self-regulation 96 . A small trial with ranolazine suggested improvement of anginal symptoms in women with microvascular angina 97 . Subsequently, in a double-blind, placebo-controlled, crossover study conducted in women with effort angina but no obstructive coronary artery disease, ranolazine produced no significant benefits except in some patients with impaired coronary flow reserve 65 .…”
Section: Microvascular Anginamentioning
confidence: 99%
“…Additional benefit may be seen from agents with alpha-blockade, such as carvedilol, in patients with coronary spasm [24]. Recently, a pilot study of Ranolazine, an anti-anginal agent that reduces calcium flow in myocytes through inhibition of the late sodium current, has been shown to improve angina in women with evidence of ischemia but no obstructive CAD [25]. While there are no clinical trials regarding the role of nitrates in patients with MCD, at least observationally, their effects on angina frequency and duration can be unpredictable in these patients.…”
Section: Discussionmentioning
confidence: 99%